Risk Mitigation Strategies for Raw Material Supply in the Animal Feed Industry in Response to Climate Change - Irham Farhan Herdiardi; Eko Ruddy Cahyadi; Alim Setiawan Slamet (Politeknik Siber Cerdika Internasional, 2026)
Background: The animal feed industry is highly dependent on agricultural raw materials such as corn, rice bran, and fine bran, which account for approximately 85–90% of total production costs. Climate change in Indonesia, characterized by unpredictable rainfall patterns and extreme weather conditions, increases supply chain risks by adversely affecting agricultural productivity. Objective: This study aims to identify and assess supply chain risks at PT XYZ associated with climate change. Specifically, it seeks to formulate evidence-based mitigation strategies to enhance supply chain resilience in the animal feed industry. Methods: This research was conducted during the first quarter of 2025 using both primary and secondary data. The analysis integrated the Supply Chain Operations Reference (SCOR), House of Risk (HOR), and Analytical Hierarchy Process (AHP) methods. Results: The findings indicate that climate variability significantly affects raw material availability, price volatility, and supply sustainability. The proposed mitigation strategies include supplier diversification, safety stock management, and the strengthening of risk monitoring systems. Conclusion: These strategies are expected to improve supply chain resilience in the animal feed industry.